KEPEMIMPINAN ORGANISASI PUBLIK VERSUS PEMBERDAYAAN - H. Abdul Rasul (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
Empowerment is a concept that should be applied in modern organizations. Emphasis on the importance of empowerment is crucial, considering that empirical phenomena show the lack of empowerment of HR personnel in providing public services. The success of determining competent leaders will be able to build a constructive work culture. The organization's vision for improvement will be translated into a variety of models, including optimizing all existing potential, including the potential of employees who work under their responsibilities. The implementation of this kind of leadership model will gradually erode the paternalistic work culture which tends to lead to many shortcomings